Sexual risk behavior and pregnancy in detained adolescent females: a study in Dutch detention centers - Jansen Lucres MC; Vermeiren Robert; Cohen-Kettenis Peggy T; Hamerlynck Sannie MJJ; Bezemer Pieter D; Doreleijers Theo AH (BMC, 2007)
Abstract Background The purpose of this study was to investigate the lifetime prevalence of teenage pregnancy in the histories of detained adolescent females and to examine the relationship between teenage pregnancy on the one hand and mental health and sexuality related characteristics on the other. Methods Of 256 admitted detained adolescent females aged 12-18 years, a representative sample (N = 212, 83%) was examined in the first month of detention. Instruments included a semi-structured interview, standardized questionnaires and file information on pregnancy, sexuality related characteristics (sexual risk behavior, multiple sex partners, sexual trauma, lack of assertiveness in sexual issues and early maturity) and mental health characteristics (conduct disorder, alcohol and drug use disorder and suicidality). Results Approximately 20% of the participants reported having been pregnant (before detention), although none had actually given birth. Sexuality related characteristics were more prevalent in the pregnancy group, while this was not so for the mental health characteristics. Age at assessment, early maturity, sexual risk behavior, and suicidality turned out to be the best predictors for pregnancy. Conclusion The lifetime prevalence of pregnancy in detained adolescent females is high and is associated with both sexuality related risk factors and mental health related risk factors. Therefore, prevention and intervention programs targeting sexual risk behavior and mental health are warranted during detention.